2004
DOI: 10.1002/kin.20000
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the pyridinolysis of aryl dithiobenzoates in acetonitrile

Abstract: The kinetics and mechanism of the aminolysis of aryl dithiobenzoates (RC( S)SC 6 H 4 Z; R = Ph) with pyridines (XC 5 H 4 N) in acetonitrile at 60.0 • C have been studied. A biphasic Brönsted plot is obtained with a change in slope from a large value (β X ∼ = 0.7-0.8) to a small value (β X ∼ = 0.2) at pK a • = 5.2, which is interpreted to indicate a change of the ratedetermining step from breakdown to formation of the zwitterionic tetrahedral intermediate, T ± , at pK a = 5.2 as the pyridine basicity is increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Such kinds of studies using physical properties such as melting points and dipole moments of benzoic acids were even reported from our laboratory . But to the authors' knowledge, the present article presents the first of its kind to observe a nonlinear Taft correlation, though there are several reports on nonlinear Hammett correlations in the literature .…”
Section: Introductionmentioning
confidence: 64%
“…Such kinds of studies using physical properties such as melting points and dipole moments of benzoic acids were even reported from our laboratory . But to the authors' knowledge, the present article presents the first of its kind to observe a nonlinear Taft correlation, though there are several reports on nonlinear Hammett correlations in the literature .…”
Section: Introductionmentioning
confidence: 64%
“…A careful examination of the literature showed that Brønsted plots highlighting two straight lines with two different slopes are rarely reported in S N Ar reactions. However, nonlinear Brønsted‐type plots have been reported for many nucleophilic substitution reactions 12–18. Koh and coworkers, for example, have observed a curved Brönsted‐type plot with β nuc decreasing from 0.71 ± 0.03 to 0.21 ± 0.06 as the pyridine basicity increases for the reaction of methyl chloroformate with X‐pyridines in acetonitrile, at 25°C [13b].…”
Section: Resultsmentioning
confidence: 99%
“…Oh et al [39] investigated the aminolysis of aryl dithiobenzoates with substituted X-pyridines in acetonitrile at 60 °C. A curved Brønsted plot was obtained with a change in slope from a large value (β x = 0.7 -0.8) to a small value (β x = 0.2) at pK a = 5.20.…”
Section: Effect Of Aniline Basicity and Mechanismmentioning
confidence: 99%